On the Zoogeographical Features of the Coleopterous Fauna of the Deserts of Turkmen S. S. R. - Kryzhanovskij, Oleg Leonidovitsch (Contributions to Entomology = Beiträge zur Entomologie, 1961)
The opinion is repeatedly expressed in zoogeographical literature about the small originality of the Turkmenistan's desert fauna, which is believed to be of the Post-Pliocene age and originated as a result of migration of Mediterranean and Central-Asiatic elements. This opinion is not confirmed by the data on Coleoptera. The insect fauna of Turkmen deserts has a large endemic nucleus including many genera and a great number of species. Particularly great is the abundance of endemics in the sandy desert fauna, which confirms the antiquity of Turanian centre of evolution of sandy deserts and the intensity of autochthonous speciation in this centre. The lowlands with solid soils (hammadas, loamy and salt deserts) have the fauna very different from that of sandy deserts; the generic endemism is insignificant here, but the number of endemic species is great. Still more endemics have the mountainous-desert fauna of Kopet-Dagh and Badghyz; it is closely related to the fauna of other low-mountainous regions of Middle Asia, Iran and North Afghanistan and many be considered as the derivative of another centre of evolution, for which the name "Irano-Bactrian" is proposed. The differences between the insect fauna of different parts of Turkmenistan can be used as a basis for the more detailed Zoogeographie delineation.